The Effect of Earthworm Meal Addition as an Atrractant in Feed on the Growth of Catfish (Clarias gariepinus) - Trisyandi Imanudin; Kiki Haetami; Evi Liviawaty; Iskandar (Grouper, 2024)
Catfish is one type of carnivorous fish that can adapt to artificial feed formulations. attractants from animal sources such as earthworm meal can be used as attractants in feed. Attractants added to feed in small amounts can stimulate appetite and fish growth. This study aims to determine the best dose of earthworm meal addition as an attractant in feed so that it affects the growth of catfish. This study used experimental method of Completely Randomised Design (RAL) with 5 treatments and 3 replicates. The treatment used was the addition of earthworm meal attractant in catfish feed at a dose of 0% (A), 5% (B), 7,5% (C), 10% (D), and 12,5% (E). The results showed that the addition of 10% earthworm meal attractant in feed (Treatment D) was the best dose for catfish growth which was able to increase absolute length growth by 6,85 cm and specific growth rate (SGR) by 4,74%/day.